Memahami Keterampilan dan Nilai Sebagai Materi Pendidikan dalam Perspektif Islam - Andhin Sabrina Zahra; Alfi Manzilatur Rokhmah; M. Yunus Abu Bakar (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Skills include a variety of mental activities, such as thinking, reasoning and problem solving. Skills can be physical, cognitive, social and emotional. Physical skills involve motor coordination, balance and flexibility, while non-physical skills involve creativity, analysis and reasoning. Social skills include interaction and communication with others, while emotional skills are concerned with recognizing and managing emotions. Skills play an important role in education, helping students prepare for the complex challenges of an ever-changing world. Global competition demands the ability to compete and innovate, while the growth of soft skills such as communication and leadership is supported by skills education. Skills education in Islam emphasizes moral and ethical values, involving religious values, character and morality in individual development. The importance of skills in education creates individuals who are ready to face the future with success, both in career and personal life. Value education in Islam includes intellectual, moral and character aspects, forming individuals who are moral and able to live their daily lives according to religious teachings.